Habitus in Pierre Bourdieu - Matuchniak-Krasuska, Anna (Hybris, 2015)
The article handles a sociological formulation of the term in the works of the eminent scholar. It also takes into account a wider, explicative context relevant to other terms (field, capital, agent, disposition, competence, distinction) used to analyze French society. It is a synchronic approach to habitus overlapping its diachronic analysis referring to the use of the term habitus in Greek, Roman and Christian philosophy found i.e. in Plato, Aristotle, Cicero, Virgil, Thomas Aquinas works.